Improving the Integration of Refugees: An Early Evaluation of a Swedish Reform - Pernilla Andersson Joona; Alma W. Lanninger; Marianne Sundström (Institute for the Study of Labor (IZA), 2015)
This paper is an early evaluation of the Swedish Establishment Reform which was enacted in 2010 with the goal of facilitating and speeding up the integration of refugees and their family into the labor market and the society. From December 1, 2010 the reform transferred the responsibility for the integration of newly-arrived refugees from the municipalities to the government funded Public Employment Service through which those eligible would get an establishment plan and a coach. The reform was motived by concern over the low employment level and slow integration of refugees. Our approach is to compare the outcomes of the treatment group, which took part in establishment activities and arrived between December 1, 2010 and December 31, 2011, to those of the comparison group, which arrived in the eleven months preceding the Reform and participated in municipal introduction programs, controlling for a rich set of observables, including country of birth and date of residence permit. Outcomes are measured in terms of employment and earnings in 2012 for the treatment group and in 2011 for the comparison group. Our data comes from registers held by Statistics Sweden and the Public Employment Service and covers all immigrants. Although there are good reasons to expect positive effects of the Reform we find no significant difference in employment or earnings between the treatment group and the comparison group.
Keywords: J15; J61; J68; 330; integration; refugees; labor market policy; treatment effect; employment; earnings; caseworkers